2024
DOI: 10.1021/acsnano.3c11734
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene Nanoplastics Activate Autophagy and Suppress Trophoblast Cell Migration/Invasion and Migrasome Formation to Induce Miscarriage

Shukun Wan,
Xiaoqing Wang,
Weina Chen
et al.

Abstract: Nanoplastics (NPs), as emerging pollutants, have attracted global attention. Nevertheless, the adverse effects of NPs on female reproductive health, especially unexplained miscarriage, are poorly understood. Defects of trophoblast cell migration and invasion are associated with miscarriage. Migrasomes were identified as cellular organelles with largely unidentified functions. Whether NPs might affect migration, invasion, and migrasome formation and induce miscarriage has been completely unexplored. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 88 publications
(156 reference statements)
0
0
0
Order By: Relevance
“…Studies targeting nanoplastic-induced abortion in women have shown that in vivo expression of ROCK1 can effectively rescue trophoblast cell migration/invasion and migrasome formation, thereby reducing abortion ( Wan et al, 2024 ), suggesting that the reproductive toxicity of some environmental exposure may be mediated by inhibition of migrasome formation.…”
Section: Function and Biological Significance Of Migrasomesmentioning
confidence: 99%
“…Studies targeting nanoplastic-induced abortion in women have shown that in vivo expression of ROCK1 can effectively rescue trophoblast cell migration/invasion and migrasome formation, thereby reducing abortion ( Wan et al, 2024 ), suggesting that the reproductive toxicity of some environmental exposure may be mediated by inhibition of migrasome formation.…”
Section: Function and Biological Significance Of Migrasomesmentioning
confidence: 99%